Pharmacotherapy handbook - Wells, Barbara G.; DiPiro, Joseph T.; Schwinghammer, Terry L. (McGraw-Hill Companies, Inc., 2012)
Essential drug data in a concise, carry-anywhere reference Pharmacotherapy Handbook, 8e provides practitioners and students with the critical information necessary to support drug therapy decision making for more than 140 diseases and disorders. Featuring a convenient alphabetized presentation, this handy guide utilizes tables, texts, figures, and treatment algorithms to make the information readily accessible and easily understood. The consistent chapter organization includes: Disease state definition Review of relevant pathophysiology Clinical presentation Diagnosis Desired outcome Treat